2018
DOI: 10.1186/s40694-018-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation associated with sexual development and female fertility in different isolates of Trichoderma reesei

Abstract: BackgroundTrichoderma reesei is one of the most frequently used filamentous fungi in industry for production of homologous and heterologous proteins. The ability to use sexual crossing in this fungus was discovered several years ago and opens up new perspectives for industrial strain improvement and investigation of gene regulation.ResultsHere we investigated the female sterile strain QM6a in comparison to the fertile isolate CBS999.97 and backcrossed derivatives of QM6a, which have regained fertility (FF1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…For T. reesei of those nutrients only glucose was shown so far to be sensed by GPCRs 64 . Additionally, we compared expression patterns under conditions of sexual development and growth on cellulose 65,66 .…”
Section: Resultsmentioning
confidence: 99%
“…For T. reesei of those nutrients only glucose was shown so far to be sensed by GPCRs 64 . Additionally, we compared expression patterns under conditions of sexual development and growth on cellulose 65,66 .…”
Section: Resultsmentioning
confidence: 99%
“…3 https://mycocosm.jgi.doe.gov/Trire2/Trire2.home.html is differentially regulated between different carbon sources (Stappler et al, 2017a). Comparative analysis showed upregulation of gpr8 under conditions of sexual development compared to growth on cellulose (>2-fold; p-value <0.005) in different T. reesei strains (Dattenböck et al, 2018). In order to gain first information on the function of GPR8 in T. reesei, we checked co-regulated genes under different conditions in publicly available datasets (Supplementary Material, Table 1).…”
Section: Gpr8 Is Regulated By Light and Associated With Metabolismmentioning
confidence: 99%
“…Although not specifically enriched, co-regulated genes in both conditions comprised numerous genes involved in secondary metabolism. Coregulation under conditions related to development (Dattenböck et al, 2018) revealed significant enrichment of genes associated with metabolism (p-value 7.8 E-04) and in particular in secondary metabolism (p-value 2.4 E-03) (Supplementary Material, Table 1). Consequently, investigation of functions of GPR8 in enzyme production and secondary metabolism should reveal the physiological role of this receptor.…”
Section: Gpr8 Is Regulated By Light and Associated With Metabolismmentioning
confidence: 99%
“…A 2019 collaborative review highlighted the present state of knowledge and raised a multitude of open questions regarding the diversity and function of fungi in marine ecosystems [13].The symbiont assemblages inside the sponge are well organized in biofilms or dense colonies and are stabilized in the skeleton network over time [14,15]. This certainly impacts their development steps and the expression of biosynthetic clusters of secondary metabolites because it is now well documented that, in fungi, secondary metabolism and life cycle among fungi are co-regulated at the genomic level [16][17][18].This idea drives us to compare the metabolic profile of fungi cultivated on a gar slants and in liquid state. The result is that solid-state cultivation often leads to larger molecular diversity than classical liquid state fermentation LSF [19][20][21].…”
mentioning
confidence: 99%
“…The symbiont assemblages inside the sponge are well organized in biofilms or dense colonies and are stabilized in the skeleton network over time [14,15]. This certainly impacts their development steps and the expression of biosynthetic clusters of secondary metabolites because it is now well documented that, in fungi, secondary metabolism and life cycle among fungi are co-regulated at the genomic level [16][17][18].…”
mentioning
confidence: 99%